Development of Internet marketing in Kazakhstan (International relations and international law Journal, 2016)
The Article is devoted to tendencies of development of Internet marketing in Kazakhstan. Today there is a set of the directions of development of marketing, and in connection with a wide circulation of technologies e-commerce began to play an important role in realization of goods through a global network and as a result there was a need for Internet marketing development. In this regard in article the reasons of emergence of Internet marketing in Kazakhstan, the problems interfering its development, a way of their decision are considered. In article theoretical approaches to the analysis of the tools used in Internet marketing in Kazakhstan are given. The interrelation and mutual influence of various factors of this direction of marketing in Kazakhstan is shown and need of its further development is noted.
Keywords: Internet marketing; Internet traffic; Internet service provider; Web site; Internet advance